Effects of lung recruitment maneuvers using mechanical ventilator on preterm hemodynamics - Adhi Teguh Perma Iskandar; Ahmad Kautsar; Anisa Rahmadhany; Risma Kerina Kaban; Bambang Supriyatno; Joedo Prihartono; Dewi I. Santoso; Tetty Yuniarti; Najib Advani; Mulyadi M. Djer; Fiolita I. Sutjipto (Paediatrica Indonesiana, 2023)
Background Lung recruitment maneuvers (LRMs) are a strategy to gradually increase mean positive airway pressure (MAP) to expand the alveoli, leading to decreased pulmonary vascular resistance and increased cardiac output (CO). However, the hemodynamic impact of LRM using assist control volume guarantee (AC-VG) ventilator mode done in preterm infants born at 24 to 32 weeks’ gestation, especially in the first 72 hours of life, remains unknown. Objective To determine the effect of LRM on right- and left cardiac ventricular output (RVO and LVO), ductus arteriosus (DA) diameter and its pulmonary hypertension (PH) flow pattern, as well as superior mesenteric artery (SMA) flow. Method This randomized, controlled, single-blinded clinical trial was performed in 24-32-week preterm neonates with birth weights of >600 grams. Subjects were allocated by block randomization to the LRM and control groups, each containing 55 subjects. We measured RVO, LVO, DA diameter, PH flow pattern, and SMA resistive index (RI) at 1 and 72 hours after mechanical ventilation was applied. We analyzed for hemodynamic differences between the two groups. Results During the initial 72 hours of mechanical ventilation, there were no significant differences between the control vs. LRM groups in mean changes of LVO [41.40 (SD 91.21) vs. 15.65 (SD 82.39) mL/kg/min, respectively; (P=0.138)] or mean changes of RVO [65.56 (SD 151.20) vs. 70.59 (SD 133.95) mL/kg/min, respectively; (P=0.859)]. Median DA diameter reduction was -0.08 [interquartile range (IQR) -0.55; 0.14] mm in the control group and -0.10 (IQR -0.17 to -0.01) mm in the LRM group (P=0.481). Median SMA resistive index was 0.02 (IQR -0.16 to 0.24) vs. 0.01(IQR -0.20 to 0.10) in the control vs. LRM group, respectively. There was no difference in proportion of pulmonary hypertension flow pattern at 72 hours (25.4% vs. 20% in the control vs. LRM group, respectively) (P=0.495). Conclusion When preterm infants of 24-32 weeks gestational age are placed on mechanical ventilation, LRM gives neither additional hemodynamic benefit nor harm compared to standard ventilator settings.